Organic matter and biomarkers: Why are samples required? - Mark A. Sephton; Andrew Steele; Frances Westall; Florence Schubotz (Proceedings of the National Academy of Sciences, 2025)
The search for evidence of past prebiotic or biotic activity on Mars will be enhanced by the return of samples to Earth laboratories. While impressive analytical feats have been accomplished by in situ missions on the red planet, accessing the capabilities of Earth’s global laboratories will present a step change in data acquisition. Highly diagnostic markers of past life are biomarkers, organic molecules whose architecture can be attributed to once living organisms. Similar organic molecular structures can also be used to identify the prebiotic steps that preceded any emergence of life. The style of modification or degradation of such organic structures indicates their agents of change, including oxidants, radiation, heating, water, and pressure. For biomarker analysis, sample return provides enhanced opportunities for sample preparation and analyte isolation. The augmentation of biomarker data with spatial information provides the opportunity for confirmatory data but is a multistep and multitechnique process best achieved here on Earth. Efficient use of returned samples will benefit from lessons learned on Earth’s ancient records and meteorites from Mars. The next decade is a time when analytical capabilities can be improved as we prepare for the delivery of carefully selected and collected extraterrestrial samples containing potential evidence of the development or even emergence of past life on Mars.